Nutritional status and dietary intake before hospital admission of pulmonary tuberculosis patients - Trong Hung Nguyen; Thi Hang Nga Nguyen; Hung Le Xuan; Phuong Thao Nguyen; Kim Cuong Nguyen; Tuyet Nhung Le Thi (AIMS Press, 2023)
Conducting research on nutritional status and dietary intake of pulmonary tuberculosis patients is essential for developing interventions in clinical nutrition practice and treatment during hospitalization, which can improve the quality of patients life. This cross-sectional descriptive study aimed to determine nutritional status and some related factors (such as geography, occupation, educational level, economic classification, etc.) of 221 patients with pulmonary tuberculosis who were examined and treated at the Respiratory Tuberculosis Department, National Lung Hospital in July 2019-May 2020. The results showed that the risk of undernutrition: According to BMI (Body Mass Index): 45.8% of patients were malnourished, 44.2% normal and 10.0% overweight/obese. According to MUAC (Mid-Upper Arm Circumference): 60.2% of patients were malnourished, 39.8% of patients were normal. According to SGA (Subjective Global Assessment): 57.9% of patients were at risk of undernutrition, of which 40.7% were at moderate risk of undernutrition and 17.2% risk of severe undernutrition. Classification of nutritional status according to serum albumin index: 50% of patients were malnourished, the rate of undernutrition of mild, moderate and severe levels was 28.9%, 17.9% and 3.2%, respectively. Most patients eat with others and eat less than four meals a day. The average dietary energy of patients with pulmonary tuberculosis in was 1242.6 ± 46.5 Kcal and 1084 ± 57.9 Kcal, respectively. 85.52% of patients did not eat enough food, 4.07% had enough, 10.41% consumed excess energy. The ratio of energy-generating substances in the diet (Carbohydrate:Protein:Lipid) was on average 54:18:28 for males and 55:16:32 for females. Most of the study population had diets that did not meet the experimental study in terms of micronutrient content. Specifically, more than 90% do not meet the requirements for magnesium, calcium, zinc, and vitamin D. The water-soluble and fat-soluble vitamins respond poorly, only about 30-40%. Selenium is the mineral with the best response rate, above 70%. Our findings revealed that the majority of the study subjects had poor nutritional status, as evidenced by diets lacking in essential micronutrients.